(3efJgi GdEOQGc aj JbGSje GdCadGcs - (3eMeO Hf CMeO GdMSjfj GdNQbj,J (B533 (3g` s
(3ChdgG (B:s
(3ai HjGf gPg GdGQV hGfbSGegG Edi GdYGeQ hZjQ GdYGeQ heG jYQV ajgG ef GNJdGa GdeWGdY hGdWhGdY s
(3BNQgG (B:s
(3BNQ eG Hg YjO GdSfGHd gh Gdjhe GdChd ef MRjQGf , jLjFhf HGdSGfHd ef RQY GdMfWI ajbQYhf YdjgG hjOYhf HGdHQcI hjJhSdhf Edi Gddg JYGdi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1852s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi s
Keywords: (3Gdadcs